Space distortion and monotone admissibility in agglomerative clustering - Akinobu Takeuchi; Hiroshi Yadohisa; Koichi Inada (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
This paper discusses the admissibility of agglomerative hierarchical clustering algorithms with respect to space distortion and monotonicity, as defined by Yadohisa et al. and Batagelj, respectively. Several admissibilities and their properties are given for selecting a clustering algorithm. Necessary and sufficient conditions for an updating formula, as introduced by Lance and Williams, are provided for the proposed admissibility criteria. A detailed explanation of the admissibility of eight popular algorithms is also given.
urn:nbn:de:kobv:11-10050664
Keywords: 330; monotonicity; admissibility; AHCA (agglomerative hierarchical clustering algorithm); space distortion